Targeting HER2 genomic alterations in non-small cell lung cancer - Jie Zeng (Elsevier, 2021)
Oncogenic mutations and amplifications in the erythroblastic oncogene B (ERBB2), or human epidermal growth factor receptor 2 (HER2), have emerged as distinct oncogenic drivers and drug targets in non-small cell lung cancer (NSCLC). Each genomic alteration occurs in 2–4% of NSCLC by next generation sequencing and is associated with constitutive HER2 activation. The most common HER2 mutations in NSCLC are exon 20 mutation A775_G776insYVMA mutation in the kinase domain and S310F mutation in the extracellular domain. Unlike in breast and gastric cancer, HER2 protein overexpression in NSCLC is not validated to be a biomarker predictive of clinical response to HER2-targeted agents. High HER2 protein overexpression by immunohistochemistry (3+) only occurs in 2–4% of NSCLC. Until now HER2-targeted agents (such as afatinib and ado-trastuzumab emtansine) only demonstrate modest clinical activity in patients with HER2-mutant NSCLC. Retrospective studies show concern for inferior clinical benefit of immune checkpoint inhibitors in HER2-mutated NSCLC. Therefore, platinum-based chemotherapy with or without an anti-angiogenesis inhibitor remains the first line standard treatment for this patient population. In May 2020 trastuzumab deruxtecan (T-DXd) received the U.S. Food and Drug Administration breakthrough therapy designation for HER2-mutant metastatic NSCLC, and was added as an option for HER2-mutant NSCLC to the NCCN guidelines V1.2021. A global phase III study of pyrotinib compared to docetaxel as a second line therapy for advanced NSCLC harboring HER2 exon 20 mutations was just opened for enrollment in September 2020. In this review, we highlight the current knowledge and perspectives on targeting-HER2 genomic alterations in NSCLC.